Nyttige normer i et ”normløst” språk - Nordgård, Torbjørn (LexicoNordica, 1999)
This article discusses certain controversial issues in connection to Norwegian writing standards: the apparent freedom of choice with respect to spelling and the lack of style definitions (radical or conservative) and pronounciation information in Norwegian dictionaries. It is argued that such information should indeed be included in dictionaries written for immigrants, and methods for adding such information based on the project NorKompLeks (Norwegian Computational Lexicon) are outlined.